2016
DOI: 10.1007/s10734-016-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Temporary contracts: effect on job satisfaction and personal lives of recent PhD graduates

Abstract: In this study, we assess the effects of temporary employment on job satisfaction and the personal lives of recent PhD graduates. Temporary employment is becoming increasingly prevalent in many sectors, but has been relatively common in academia, especially for early career scientists. Labor market theory shows temporary employment to have a conspicuous negative influence on the job satisfaction and well-being of employees, but also identifies groups that may be exempt from these negative influences, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 37 publications
6
71
2
7
Order By: Relevance
“…Furthermore, where there is strong motivation to participate and learn, the incorporation of a threefold peer learning model can be a powerful development tool. In a profession where there is a low level of control (Waaijer et al, 2016), placing training opportunities within the control of those who need them is a positive step forward. Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, where there is strong motivation to participate and learn, the incorporation of a threefold peer learning model can be a powerful development tool. In a profession where there is a low level of control (Waaijer et al, 2016), placing training opportunities within the control of those who need them is a positive step forward. Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why both groups report similar levels of job satisfaction on average and the neglect of the honeymoon-effect might be responsible for the inconclusive evidence found in different studies (e.g. Waaijer, Belder, Sonneveld, van Bochove, & van der Weijden, 2016;Zeytinoglu et al, 2013). This phenomenon could also explain the inconclusive results regarding TAW and job satisfaction.…”
Section: Heterogeneity Between Studies and Related Limitations Of Thementioning
confidence: 93%
“…These career prospects affect academics: Höge, Brucculeri, & Iwanova (2012) showed that temporary employment among postdoctoral researchers in Germany, Austria and the UK decreases well-being due to insecurity. Among PhD graduates in the Netherlands, temporary employment decreases the job satisfaction (Waaijer, Belder, Sonneveld, van Bochove, & van der Weijden, 2016). These effects of temporary employment in academia are also seen as a problem by leading opinion makers in science, as they decrease the attractiveness of academic careers (Waaijer, 2013).…”
Section: Contingent Academic Careers?mentioning
confidence: 99%